Strengthening Environmental Awareness through Project-Based Learning: A Global and National Review, and Implications for Indonesian Primary Schools - Esty Setyo Utaminingsih; FR. Wuriningsih; Idammatussilmi Idammatussilmi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
Escalating environmental challenges have underscored the need to cultivate environmental awareness from primary schooling, yet classroom instruction often offers limited authentic engagement with local ecological problems. This systematic review synthesizes recent empirical evidence (2020-2025) on the effectiveness of Project-Based Learning (PBL) in strengthening primary students' environmental knowledge, attitudes, and pro-environmental behaviors, and identifies enabling and constraining conditions for its implementation. Searches of Scopus, Web of Science, ScienceDirect, and SAGE returned more than 200 records, which were screened to identify 7 empirical studies for synthesis. Across these studies, PBL consistently improved environmental outcomes in cognitive, affective, and behavioral domains, with several reports showing statistically significant pre-post or group differences and moderate-to-very-strong positive associations between PBL participation and indicators of environmental awareness (r = 0.52-0.96). Successful implementation was supported by school leadership and an enabling culture, teacher preparedness and collaboration, and curricular flexibility, whereas limited instructional time, resource constraints, and insufficient teacher readiness were recurring barriers. Overall, PBL is an effective approach to strengthening environmental awareness in primary education when it is institutionally supported and adapted to local contexts.